Synthesis and characterization of two metallic spin-glass phases of FeMo4Ge3 - Baker, P; Battle, P; Blundell, S; Grandjean, F; Lancaster, T; Long, G; Oldham, S; Prior, T (American Physical Society, 2008)
Polycrystalline samples of FeMo4Ge3 have been synthesized by the reduction of an oxide mixture at 1248 K and characterized by a combination of diffraction, muon spin relaxation (μ+SR), Mössbauer spectroscopy, magnetometry, transport, and heat-capacity measurements. The compound adopts a tetragonal W5Si3 structure (space group I4/mcm); the iron and molybdenum atoms are disordered over two crystallographic sites, 16k and either 4a or 4b. The synthesis conditions determine which fourfold site is selected; occupation of either leads to the presence of one-dimensional chains of transition metals in the structure. In both cases, the electrical resistivity below 200 K is ~ 175μΩ cm. The dc magnetization rapidly rises below 35 K (Fe/Mo on 16k and 4b sites) or 16 K (16k and 4a sites), and a magnetization of 1μB or 0.8B per Fe atom is observed in 4 T at 2 K. The ac susceptibility and the heat capacity both suggest that these are glasslike magnetic transitions, although the transition shows a more complex temperature dependence (with two maxima in X'') when the 4b sites are partially occupied by iron. No long-range magnetic order is thought to be present at 5 K in either structural form; this has been proven by neutron diffraction and μ+SR for the case when Fe and Mo occupy the 16k and 4b sites.